(3GdJPcQI HCUhd GdMSGH hGdaQGFV (B( (3GdehGQjK(B)s - (3Ydj Hf GdNVQ Hf GdMSf GdbQTj GdYKeGfj, CHh GdMSf,J (B459 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hdi GdfYe , hGdeMQc ajeG bSe , hGdeHJOF HGdcQe Cbhd CeG HYO , SCdJ CjgG GdCN GdSjO Gdabjg GdaGVd Cf GQJH dcd CUdkG ai GdMSGH s
(3BNQgG (B:s
(3abO GLHJc Edi edJeSc ajLH Cf fHSW ai GdYPQ hJUdM eG hLOJg ef ZdW faYfG Gddg hEjGc hgh MSHfG hfYe Gdhcjd s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B284s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI(B((3aQGFV (B10) s
Keywords: (3abg GdePGgH GdCNQis